Acute mesenteric ischemia associated with Covid-19: case series - Tafur-Hoyos, Brenda Aurora (2023)
Introduction: Patients with Covid-19 may present most serious complications, pulmonary thromboembolism and acute mesenteric ischemia (AMI) have been described. These thrombotic events are now more common in the context of the Covid-19 pandemic, because patients have to state of hyperinflammation and transient hypercoagulability.  Case of Report: AMI manifestation are abdominal pain and other atypical gastrointestinal symptoms. Patients with severe and critical symptoms of Covid-19, have elevated levels of D-dimer and coagulation disorders. The paper described a fatal outcome of to two patients of Covid-19 that presented with mesenteric ischemia. The objective of this report is to emphasize the importance of early recognition of this complication, which has high mortality rates. The first series of Covid-19 cases that attended IMA in northern Peru is described. Two male patients, 48 and 67 years old, with a subacute course presented respiratory symptoms. However in subsequent days, their symptoms worsened presenting, with abdominal pain, high levels of D-dimer, and coagulation disorders. Both presented AMI, however, this diagnosis was not suspected until they were operated. Conclusion: The patients with Covid-19 who present atypical gastrointestinal symptoms, this disease should be considered in the diagnosis. It is important to know how to recognize it early.